Efektifitas Faktor Organisasi dan Motivasi terhadap Kinerja Perawat dalam Pelaksanaan Pencegahan dan Pengendalian Infeksi (PPI) - Martha Oktavia Setyaningrum; Nursalam Nursalam; Rizki Fitryasari PK (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of organizational factors and motivation on the performance of nurses in implementing PPI. The method used is descriptive-analytic with a cross-sectional approach. This study used a questionnaire conducted in 15 inpatient rooms at Haji Surabaya Hospital with 126 nurses. The sample collection technique uses purposive sampling. The data analysis technique uses descriptive statistical analysis and multiple linear regression analysis. The results showed that the results of the F test hypothesis on organizational factor variables (X1) and motivation (X2) had a value of F < (alpha) 0.05, namely 0.004 and 0.000 so that corporate and motivational factor variables had a significant influence on nurse performance variables in implementing PPI. In conclusion, organizational and motivational factors have a substantial effect on the performance of nurses in the implementation of PPI. Keywords: Organizational Factors, Nurse Performance in Implementation of Infection Prevention and Control (PPI), Motivation